Horizontal ridge augmentation with porcine bone-derived grafting material: a long-term retrospective clinical study with more than 5 years of follow-up - Choi, Jin-Won; Hwang, Soo-Shin; Yun, Pil-Young; Kim, Young-Kyun (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2023)
The purpose of this study was to evaluate the outcomes of implants placed in horizontally augmented alveolar ridges using porcine bone grafts and to investigate the long-term stability of the porcine bone grafts. A retrospective analysis was conducted on 49 sites that underwent horizontal ridge augmentation using porcine bone grafts and implant placement with a follow-up period longer than 5 years. Furthermore, additional analysis was conducted on 24 sites where porcine bone grafts were used exclusively for horizontal ridge augmentation and implant placement. The mean follow-up period after prosthesis loading was 67.5 months, with a mean marginal bone loss of 0.23 mm at 1 year and a cumulative mean marginal bone loss of 0.40 mm over the entire follow-up period. Of the 49 implants, 2 were lost and 3 did not meet the success criteria, resulting in a survival rate of 95.9% and a success rate of 89.8%. In 24 sites, the mean marginal bone loss was 0.23 mm at 1 year and 0.41 mm at 65.8 months, with 100% survival and success rates. Porcine bone grafts can be successfully used in horizontal ridge augmentation for implant placement in cases of ridges with insufficient horizontal width.